مشاركة ليبيا في الحروب العربية الاسرائيلية ( 1948م- 1973م ) - عزوزي فتيحة; د/ بوقرين عيسى (جامعة عمار ثليجي الاغواط, 2024)
الملخص باللغة العربية تتناول هذه الدراسة موضوعا هاما يتمثل في مشاركة ليبيا في الحروب العربية الإسرائيلية 1948 / 1973 ، حيث أدت ليبيا دورا بارزا لاشتراكها في الحروب الثالثة و واجهة دول قوية من بريطانيا و الاتحاد السفياتي و الولايات المتخذة الأمريكية. و قد تميزت الدولة الليبية بمساعدها للشعب الفلسطيني من ألبسة و غذاء ، و قد أدت هذه الحروب إلى قتل الجيوش العربية منذ من نشوب أول حرب سنة 1948 . و في حرب 1967 كان نتاجها بفوز مص على إسرائيل أما حرب أكتوبر 1973 فتعود أسبابها إلى استرداد أراضي مصر و سوريا المحتلة من طرف إسرائيل ما أسفرت هذه الحرب الأخيرة إلى وقف إطلاق الار بين إسرائيل و الدولتين مصر و سوريا . Abstract This study addresses an important topic: Libya's participation in the Arab-Israeli wars from 1948 to 1973. Libya played a prominent role in these three wars, facing powerful nations such as Britain, the Soviet Union, and the United States. The Libyan state was distinguished by its support for the Palestinian people, providing clothing and food. These wars resulted in the loss of many Arab soldiers, starting with the first war in 1948. In the 1967 war, Egypt emerged victorious over Israel. As for the October War of 1973, its cause was to reclaim Egypt's and Syria's lands that had been occupied by Israel. This last war resulted in a ceasefire between Israel and the two nations, Egypt and Syria.